Persuasive Strategies Used by Multi-Level Marketing and Insurance Agents - Wenty Andriani; Leni Marlina (English Language and Literature, 2019)
This study examines the types of persuasive strategies used by Multi-Level Marketing (MLM) and insurance agents in influenced target costumers. The purpose of this study besides to find out the types of persuasive strategies used by MLM and insurance agents also to find out the differences and the similarities of the types of persuasive strategies used by the agents. This study is a descriptive qualitative method because it explains and compares the types of persuasive strategies used by MLM and insurance agents to see the differences and similarities. The result of the study shows that (1) the types of persuasive strategies that mostly used by MLM and insurance agents are Logic and Evidence (2) the highest component used by MLM agents is Specific Evidence; however, insurance agents used Credible Evidence.